Prognosis in early stage cutaneous T‐cell lymphoma treated with psoralen plus ultraviolet A irradiation and low‐dose interferon‐α: Long‐term efficacy and survival according to conventional and emerging clinical endpoints. Issue 10 (9th August 2022) - Rupoli, Serena; Goteri, Gaia; Morsia, Erika; Torre, Elena; Giantomassi, Federica; Campanati, Anna; Offidani, Anna Maria; Molinelli, Elisa; Brandozzi, Giuliano; Serresi, Stefano; Giacchetti, Alfredo; Bugatti, Leonardo; et al.
Abstract: Patients with early stage cutaneous T cell lymphoma (CTCL) usually have a benign and chronic disease course, characterized by temporally response to conventional skin directed therapies and intrinsic possibility to evolve. Using the combination of psoralen plus ultraviolet A irradiation (PUVA) and low‐dose interferon‐α (INF), the principal treatment goal is to keep confined the disease to the skin, preventing disease progression. Among 87 patients with early stage IA to IIA MF treated with low‐dose IFN‐α2b and PUVA in our center, complete remission (CR) were reported in 70 patients (80.5%) and the overall response rate (ORR) was 97.8% ( n  = 85), with a median time to best response to therapy of 5 months (range, 1–30). Among the responders, only the 8% of patients had a relapse with major event. The median follow‐up was 207 months (range, 6–295). Survival data showed a median overall survival (OS) not reached (95% CI; 235‐NR months), a disease free survival (DFS) of 210 months (95% CI; 200–226 months) and a median time to next treatment (TTNT) of 38.5 months (95% CI, 33–46 months). The long follow up of this study verifies our preliminary results already published in 2006 and confirms the efficacy of INF‐PUVA combination therapy in a real world setting, according conventional (OS and DFS) and emerging (TTNT) clinical endpoint of treatment efficacy.